"Carry our colours and defend our interests under the skies of other Continents". Argentinian Commercial aviation policy in the Peronista decade (1945–55). Issue 1 (June 2019) - Piglia, Melina
In the context of the challenges posed by the end of the Second World War and the early post-war period, the Argentinian governments foresaw aviation as a pillar of its national and international presence. Argentina created the Air Force, nationalised ground aerial infrastructures, placed domestic flights under state control and in 1950, all Argentinian airlines were nationalised and merged into a single state-owned enterprise: Aerolíneas Argentinas . Meanwhile, Argentinian leadership aggressively negotiated bilateral agreements. This paper analyses aviation policy (both domestic and international) of the first Peronista decade from 1945 to 1955, framing it as a response to limit USA expansion into South America, building Argentinian hegemony in the region and consolidating the ongoing process of industrialisation and economic autonomy.